Fabrication, characterization and mechanical behaviour of Tamarindus indica fruit fibre-reinforced polymer composites - Sreenivasaraja Nagarajan; Kathiresan Marimuthu; Prashanth Shanmugam; Moganapriya Chinnasamy (Polímeros, 2025)
Abstract In this work, a study was undertaken to explore the possibility of using leftover tamarind fruit fibres as reinforcement in PLA and HDPE matrix. PLA and HDPE polymers form minimum 75% of the total polymers used in the composites. PLA and HDPE was mixed with natural fibres (5 wt.%, 10 wt.%, 15 wt.%, 20 wt.% and 25 wt.%,) individually and also as a hybrid filler to enhance its mechanical properties. Characterizations, mechanical behaviour and microscopic investigation were performed to understand the excellent mechanical properties and good chemical resistance of the prepared composites, which demonstrated potential suitability for semi-structural applications.